Exploring multimodal writing in secondary English classrooms: a literature review. Issue 4 (12th November 2018) - Nash, Brady
Abstract : Purpose: This paper aims to explore recent research (2007-2017) on the implementation of multimodal writing instruction in secondary English courses. It seeks to highlight the varied ways in which theoretical conceptions of multimodality have been implemented in writing instruction and the impacts of these implementations on students' experiences in classrooms. Design/methodology/approach: The author used a keyword search of relevant academic databases to identity articles within the search parameters. This was followed by bibliographic branching to identify additional articles and two rounds of open coding to identify themes for analysis. Findings: The literature revealed a diversity of approaches to incorporating multimodal writing in classrooms; teachers mixed modalities within assignments, paired writing in print with multimodal composition and redesigned entire units or courses around multimodality. Studies showed the impact of multimodality on student learning through shifts in conceptions of communication, increases in student engagement, composition for real audiences and an increased role for students' interests and identities. Practical implications: This review has implications for teachers and researchers interested in developing multimodal writing curricula. It highlights the specific ways in which multimodal writing can be incorporated into instruction and the changes in student learning that result from this shift. Originality/value: While theoretical writing on multimodality is abundant, multiple researchers have noted the difficulty of finding research on classroom implementations of multimodality (Howell et al., 2017 ;Smith, 2017 ). This review is intended to address this difficulty by contributing to a body of literature that teachers and scholars can draw on as they conceptualize and design multimodal writing experiences for students in the future.